THE EFFECT OF RETURN ON EQUITY AND DEBT TO EQUITY RATIO ON STOCK PRICES IN THE COMPANY TRANSPORTATION SUB SECTOR LISTED ON THE INDONESIA STOCK EXCHANGE FOR THE 2015-2019 PERIOD - Iskandar Zulkarnain; Nanda Sulistiyowati; Sjukun (International Journal of Social Science, 2022)
This research aims to analyze the effect of the Return on Equity, Debt to Equity Ratio and towards stock price in the Transportation sub-rector in 2015-2019. The associative quantitative method is used as a research method using secondary data. The population of this research consists of 41 companies and by purposive sampling technique, 16 companies are obtained as a sample. Multiple linear regression is used by the researcher as a data analysis technique. The results showed that partially Return On Equity had a positive and significant effect on stock prices. Debt To Equity Ratio has a positive and significant effect on the stock price. Simultaneously or jointly Return On Equity and Debt To Equity Ratio affect the Share Price of Transportation companies listed on the Indonesia Stock Exchange from 2015 to 2019. The coefficient of determination of 0.466 means the ability of independent variables to explain the variation of dependent variables by 46.6%, while the remaining 53.4% is explained by other variables outside the research model